A Computer Game Based Approach for Increasing Fluency in the Speech of the Autistic Children - Anwar, A.; Rahman, M. M.; Ferdous, S. M.; Anik, S. A.; Ahmed, S. I. (2011 IEEE 11th International Conference on Advanced Learning Technologies, 2011)
Autism is a complex developmental disability that typically appears during the first three years of life. This is the result of a neurological disorder that affects the functioning of human brain. Children diagnosed with autism often are self-absorbed and seem to exist in a private world where they are unable to successfully communicate and interact with others. Sometimes they have difficulties in developing speaking skills and understanding what others say to them. Lack of fluency in the speech is one of the most frequently found problems with autistic children. The traditional methods for increasing fluency were found to be monotonous and hence, not much successful during our three months of observations over the participants of Autism Welfare Foundation (AWF) at Dhaka. Therefore, we developed an interactive computer game for the autistic children for improving the fluency in their speech. Our game produced encouraging results over a participant during three months of observation. In this paper, we describe our project and the outcomes.